Mortal and Immortal Souls, Ghosts and the (Restless) Dead in Ancient Mesopotamia. Issue 4 (21st April 2016) - Scurlock, JoAnn
Abstract: Ever since their original creation from mortal clay mixed with the flesh and blood of an immortal god, Ancient Mesopotamians had a part of themselves that survived death. We call this death‐surviving part the soul. Ancient Mesopotamians, however, like ancient Greeks, understood this surviving bit as a complex of elements with differing possibilities of survival or, if you will, multiple souls of differing levels of immortality. Of these spiritual essences, one is what we would call a ghost. Unfortunately this was not, like our own ghosts, limited to haunting houses, but fully capable of doing serious harm to the living. Partly this was because the dead, although no longer living, continued to feel hunger and thirst without being able to provide food and drink for themselves, and partly it was because certain bad deaths produced very unhappy ghosts. Ancient Mesopotamians dealt with this problem using a multiplex strategy. Former members of the family received a continual round of offerings as long as the family survived to supply them. If afflicted with spectral attack, there were healing rituals designed to deal with the troublemaker. Finally, special entertainment was provided at festivals of the dead (similar to our Halloween) when ghosts were released from the Netherworld prison to which they were confined for the rest of the year. These festivals also provided an opportunity for last visits with dead family members, consultation with the dead for advice (necromancy) and even witchcraft to revenge oneself on personal enemies. In what follows, I will give a brief overview of the current state of knowledge, with suggestions for further reading.